Populists and planners: 'We are the people. Who are you?'*. (February 2020) - Sager, Tore
The purpose of this article is to offer planning scholars a basis for criticizing authoritarian populism and not limiting ideological critique to neoliberalism. Authoritarian populism is anti-elitist, anti-pluralist and excluding in that the authentic people includes only part of the population. Authoritarian populists imagine a homogeneous people whose will determines policy. The article deals with confrontations and contact points between communicative planning theory and populist currents. It distils several core themes from five authoritative collections of works on planning theory and examines their relations with populist ideas. Authoritarian populism is an incomplete ideology that can fuse with various other ideologies. Amalgamations of populism and neoliberalism pose new challenges to participatory planning. Authoritarian populism criticizes planning institutions for blocking the immediate realization of the will of the people and being sympathetic to social diversity and cultural influence threatening heartland values. Neoliberalism is opposed to the welfare policies, equity goals, growth restrictions and other public interventions associated with spatial planning. Joint pressure from the two ideologies may alter the planning of liberal democracies in an autocratic direction.